Sistema de gestión para la administración de proyectos del departamento de planeamiento de la Universidad Técnica de Cotopaxi - Ilbay Yupangui, Miryam Fabiola (2018)
The Computer System for the Management of Investment Projects, is a support tool mainly for the Planning Department, since its main objective is to facilitate the creation of projects by research professors, provide a control follow-up and generate reports of the existing projects based on a logical framework matrix that covers the different activities, for the development of the computer system interface, a SENPLADES Methodological Guide was used, with information on the existing projects in the Planning Department of the Cotopaxi Technical University, the information that covers is stored in the SQL Server database, and for the programming the Visual Basic.Net language was manipulated, also to the enter to the system the different users will have a username and password, since by this way they will be able to access the required searching, and know the features that it offers such as: project information, departments and users records, create projects, track and generate reports. To carry out the follow-up, a budget value is chosen since it is created when the project is created, generating an amount for each one of the existing components within it. An important aspect of the computer system is that the beneficiaries of the projects can approve or reject the project sent by teacher researchers and by this way giving continuity to the job.